Interpretasi Etnomatematika: Struktur Geometri pada Batu Kubur Tradisional Sumba Barat - Ayu, Mitra Permata; Ledi, Dian Fransiska; Ege, Emirensiana Dappa; Sabawaly, Diana Rebi (Jurnal Penelitian dan Pembelajaran Matematika, 2025)
Mathematics in general is just a science of counting, without realizing it, mathematics has been integrated with culture for a long time. Mathematics has been applied in forming traditions and cultures of a region such as making traditional grave stones. This study aims to reveal the geometric structure used by the West Sumba community in making traditional grave stones. The research methods used are observation, interviews and documentation. The results of the study show that 1) there are traditional grave stones as historical relics that are still maintained and preserved; 2) there are ethnomathematic activities such as measuring, drawing patterns on grave stone motif carvings and building grave stones to make them sturdy; 3) the geometric structures found are such as flat shapes (squares, rectangles, trapezoids and triangles) and spatial shapes (cylinders).